THE EFFECT OF MOLASSES AND TOFU DREGS ON THE GROWTH OF BLACK SOLDIER FLY MAGGOTS (Hermetia illucens) - Wildhatu Dzati Fiqhul Khuluqiyyah; Nurul Jadid Mubarakati; Husain Latuconsina (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
The utilization of organic waste in Indonesia has not been fully optimized, but one technique that can be used is bioconversion, which involves the use of organisms such as the maggot black soldier fly (Hermetia illucens) to convert the waste. Organic waste sources, such as molasses and tofu dregs, can be used for this purpose. The aim of this study was to investigate the growth of BSF maggots using molasses and tofu dregs media. A completely randomized design (CRD) with four treatments and six replications was used, including a control treatment using fruit and vegetable waste (P0), 100% molasses (P1), 50% molasses and 50% tofu dregs (P2), and 100% tofu dregs (P3). The data were analyzed using the SPSS program, and the results indicated that the P0 treatment produced the highest weight and length of 0.13 grams and 17 millimeters, respectively. Further analysis using DMRT showed that P0 was the best medium for maggot growth. The treatment with the highest maggot nutritional content was P0, with 9.57% protein and 5.99% fat. The treatment with the highest carbohydrate content was P2, at 22.04%. Future research can investigate other media and ratios to further optimize the growth of the maggot black soldier fly (Hermetia illucens).Keywords: growth, fruit and vegetable waste, maggot, molasses, tofu dregs